Study of Total Phenol, Flavonoids and Antioxidant Activity of Kidney Beans (Phaseolus Vulgaris L.) at Various Length of Germination Times - Wisaniyasa, Ni Wayan; Darmayanti, Luh Putu Trisna (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 6 No 1 (2019): Scientific Journal of Food Technology (March), 2020)
The purpose of this study are 1) to find out whether the length of germination times affects on the total phenol, flavonoids and antioxidant activity of kidney bean sprouts 2). To determine the total phenol, flavonoids and antioxidant activity of kidney beans at various germination times 3). Determine the best germination time and the nutrient composition. The germination time in this study were 0, 24, 36, 48, 60 and 72 hours. This study used a completely randomized design with three replications in order to obtain 18 experimental units. Data analysis based on ANOVA, if the treatment affects the observed varables then tested with Duncant. The results showed that the length of germination time very significant effect on the total phenols, flavonoids and antioxidant activity of kidney bean sprouts. Total phenol content of 4.46-6.33%, flavonoid levels of 1.17-9.23 mg/100 g QE, and antioxidant activity of 53.91-65.10 ppm (IC 50%). The best length of germination time was 48 hours with nutritional composition: water content 64.83%, ash 0.94%, fat 3.69%, protein 25.61% and carbohydrate 4.93%.